Assistance in management of network-based school administration e-archives (cloud) - Lelahester Rina; Agus Sugiarto (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
The development of science and technology has had a major impact on all aspects of work, one of which is the management of office administration. Office work that continues to change is how to manage office document archives carried out electronically for work efficiency. The conditions at the Satya Wacana Christian High School Salatiga in the initial interviews and observations showed that the process of data input and filing of report cards and diplomas was still carried out by being bundled and stored on office furniture. School administrative documents have not been backed up electronically to anticipate archive loss and data security. This resulted in the need for physical document archive storage space quite a lot, including filing cabinets and archive rooms. This activity has the aim of providing understanding and skills of electronic archives (e-archive) in managing school administration through the network (cloud). The program implementation method is carried out by providing training and assistance in managing school administration electronically based on a network (cloud). The results of the activity show that education personnel is able to manage school administrative documents electronically using the network (cloud) well. Education staff can group several archives into active and inactive archives and their management is directed at electronic documents through scanning or scanning for digital archive management.